2009
DOI: 10.1371/journal.pone.0005867
|View full text |Cite
|
Sign up to set email alerts
|

The QKI-6 and QKI-7 RNA Binding Proteins Block Proliferation and Promote Schwann Cell Myelination

Abstract: BackgroundThe quaking viable (qkv) mice have uncompacted myelin in their central and peripheral nervous system (CNS, PNS). The qk gene encodes 3 major alternatively spliced isoforms that contain unique sequence at their C-terminus dictating their cellular localization. QKI-5 is a nuclear isoform, whereas QKI-6 and QKI-7 are cytoplasmic isoforms. The qkv mice harbor an enhancer/promoter deletion that prevents the expression of isoforms QKI-6 and QKI-7 in myelinating cells resulting in a dysmyelination phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 49 publications
(79 reference statements)
4
46
0
Order By: Relevance
“…Kip (Larocque et al, 2009) as well as that of pro-myelinating transcription factors and myelin proteins (MAG and P0) (Monuki et al, 1989;Parkinson et al, 2004), while reducing the expression of c-Jun, a negative regulator of myelination (Parkinson et al, 2008), and other markers of non-myelinating SCs such as p75 and Ncadherin (Monje et al, 2009;Morgan et al, 1991). Surprisingly, treatment with cAMP dramatically downregulated the expression of MLCK and the level of phosphorylated MLC (MLC-P), indicating an overall reduction of myosin II activity in promyelinating SCs.…”
Section: Elevation Of Camp In Scs Downregulates Mlck and Mlc Phosphormentioning
confidence: 99%
“…Kip (Larocque et al, 2009) as well as that of pro-myelinating transcription factors and myelin proteins (MAG and P0) (Monuki et al, 1989;Parkinson et al, 2004), while reducing the expression of c-Jun, a negative regulator of myelination (Parkinson et al, 2008), and other markers of non-myelinating SCs such as p75 and Ncadherin (Monje et al, 2009;Morgan et al, 1991). Surprisingly, treatment with cAMP dramatically downregulated the expression of MLCK and the level of phosphorylated MLC (MLC-P), indicating an overall reduction of myosin II activity in promyelinating SCs.…”
Section: Elevation Of Camp In Scs Downregulates Mlck and Mlc Phosphormentioning
confidence: 99%
“…During differentiation of glial cells, QKI proteins regulate expression of the tumor suppressor p27, Krox20 (a transcription factor critical for myelination in the peripheral nervous system), Myelin Basic Protein (MBP) and Myelin-Associated Glycoprotein (MAG). [21][22][23][24][25] C. elegans contains two QR proteins, ASD-2 (alternative splicing defect) and GLD-1 (defective in germ line development). While relatively little is known about ASD-2, 26 GLD-1 functions to control several decisions during germ line development, such as the choice between mitosis and meiosis or spermatogenesis and oogenesis.…”
Section: The Qr Proteins: Versatile Mrna Regulators With a Wide Rangementioning
confidence: 99%
“…In mammalian myelin-producing cells, QKIs promote expression of factors required for terminal differentiation and myelin production (MBP, MAG and Krox 20). 21,[23][24][25] In contrast, in the worm germ line GLD-1 represses factors (such as GLP-1/Notch, TRA-2, and possibly OMA-1/2, or LIN-45/Raf) whose ectopic expression would interfere with the progression through meiosis and gametogenesis. 30,32,34 Similarly, in the early fly mesoderm, How represses expression of factors that can otherwise activate abnormal cell signaling, interfere with normal mesoderm formation, and perhaps induce an alternative cell fate (Fig.…”
Section: Regulation Of Differentiation In Uncommitted Cells By Quakinmentioning
confidence: 99%
“…Drosophila proteins marked with a * were already identified as being expressed in glial cells by Altenhein et al [127] and proteins marked with ** were identified by Freeman et al [126] septate junction formation by splicing and possibly post-translational control of the nuclear access of splicing factors appears also evolutionary conserved. The HOW homolog Quaking is needed for proper development of myelinated nerves and has also been linked to the control of splicing [128][129][130][131]. This suggests that elucidation of the mechanism underlying the action of the Crn/HOW complex will shed some light on the biology of myelination.…”
Section: Discussionmentioning
confidence: 99%